2013
DOI: 10.1111/acer.12227
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol (EtOH) Exposure Alters the Sensitivity of the Adult Dentate Gyrus to Acute EtOH Exposure

Abstract: Prenatal EtOH exposure alters the sensitivity of the adult dentate gyrus to acute EtOH application producing a long-lasting tolerance to the inhibitory effects of EtOH. This decreased sensitivity may provide a mechanism promoting the formation of drug-associated memories and help explain the increased likelihood of developing an alcohol dependency often observed in individuals with FASDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Neuroimaging studies also revealed overall brain volume reductions in FASD patients (Guerri et al, 2009). In agreement with human findings, rodent models of PAE have shown reductions in brain and body weight and reduced litter size in alcohol-exposed offspring (Abbott et al, 2016;An and Zhang, 2015;Chappell et al, 2007;Comeau et al, 2014;Dasgupta et al, 2007;El Shawa et al, 2013;Helfer et al, 2014). Nevertheless, other studies reported no differences in litter size or pup weight in rodent models of alcohol exposure in utero, which is consistent with our results (Allan et al, 2003;Barbier et al, 2009;Brady et al, 2012;Choi et al, 2005;Cullen et al, 2014;Hausknecht et al, 2014;Kleiber et al, 2011;Savage et al, 2002).…”
Section: Animal Model and Behavioral Effects Induced By Prenatal And supporting
confidence: 91%
“…Neuroimaging studies also revealed overall brain volume reductions in FASD patients (Guerri et al, 2009). In agreement with human findings, rodent models of PAE have shown reductions in brain and body weight and reduced litter size in alcohol-exposed offspring (Abbott et al, 2016;An and Zhang, 2015;Chappell et al, 2007;Comeau et al, 2014;Dasgupta et al, 2007;El Shawa et al, 2013;Helfer et al, 2014). Nevertheless, other studies reported no differences in litter size or pup weight in rodent models of alcohol exposure in utero, which is consistent with our results (Allan et al, 2003;Barbier et al, 2009;Brady et al, 2012;Choi et al, 2005;Cullen et al, 2014;Hausknecht et al, 2014;Kleiber et al, 2011;Savage et al, 2002).…”
Section: Animal Model and Behavioral Effects Induced By Prenatal And supporting
confidence: 91%
“…To induce LTD, we administered a train of low-frequency stimuli (LFS; 1 Hz; 900 pulses; Christie et al 1996). For LTP, short trains of high-frequency stimuli (HFS; 50 pulses at 100 Hz) were delivered four times with a 30-s intertrain interval (Helfer et al 2014). Following the application of conditioning stimuli, we resumed single-pulse stimulation (0.067 Hz) for an additional 60 min.…”
Section: Animalsmentioning
confidence: 99%
“…For instance, gonadotropin-releasing hormone (GnRH) can regulate estradiol synthesis, spine density, and the expression of synaptic proteins through both genomic and nongenomic mechanisms (Fester et al 2012;Kotitschke et al 2009). The mechanisms involved in spine generation are important to understand, because a number of sex-specific differences in synaptic plasticity have been reported in a variety of neuropathological processes that range from fetal alcohol spec-trum disorders (FASD) to Fragile-X syndrome (Bostrom et al 2015;Helfer et al 2012Helfer et al , 2014Yau et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation